Trends in U.S. Family Income Mobility, 1969-2006 - Katharine Bradbury (Federal Reserve Bank of Boston, 2011)
Much of America's promise is predicated on economic mobility - the idea that people are not limited or defined by where they start, but can move up the economic ladder based on their efforts and accomplishments. Family income mobility - changes in individual families' income positions over time - is one indicator of the degree to which the eventual economic wellbeing of any family is tethered to its starting point. In the United States, family income inequality has risen from year to year since the mid-1970s; given this rising cross-sectional inequality, changes over time in mobility determine the degree to which long-term income is also increasingly unequally distributed. Using data from the Panel Study of Income Dynamics and a number of mobility concepts and measures drawn from the literature, this paper examines family income mobility levels and trends for U.S. working-age family heads and spouses during the time span 1969-2006, based on a post-tax, post-transfer concept of income adjusted for family size. By most measures, mobility is lower in more recent periods (1995-2005) than in the late seventies and the eighties (the 1977-1987 or 1981-1991 periods). Comparing results based on pre-government income suggests that an increasingly redistributive tax and transfer system contributed to rising mobility into the 1980s, but that its impact has since waned. Overall, the evidence indicates that over the 1969-to-2006 time span, family income mobility across the distribution decreased, families' later-year incomes increasingly depended on their starting place, and the distribution of families' lifetime incomes became less equal.
Keywords: D31; D63; I32; J15; 330; Income mobility; income inequality; income distribution